2015
DOI: 10.1093/trstmh/trv014
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Chlamydia trachomatis infection in Samoan women aged 18 to 29 and assessment of possible risk factors: a community-based study

Abstract: The prevalence of CT infection in these Samoan women is very high. Further studies, including investigating the prevalence of CT infection in men, and strategies for sustainable control are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 25 publications
1
23
0
Order By: Relevance
“…This outcome might reflect, at least in part, poor access to and utilisation of STI servicesthere is very limited capacity in the Middle East and north Africa for STI prevention and treatment, not to mention C trachomatis screening and broader sexual health programmes. As observed elsewhere, such as in Alaskan Eskimo populations 194 and populations in South Pacific Islands, 195 poor C trachomatis diagnosis and specific treatment can result in unusually high prevalence, 194,196 probably because C trachomatis is largely asymptomatic, 4 and if untreated, shedding can persist even for years, 197 thereby increasing the potential for reinfection within couples 198 and for transmission in the population.…”
Section: Discussionmentioning
confidence: 89%
“…This outcome might reflect, at least in part, poor access to and utilisation of STI servicesthere is very limited capacity in the Middle East and north Africa for STI prevention and treatment, not to mention C trachomatis screening and broader sexual health programmes. As observed elsewhere, such as in Alaskan Eskimo populations 194 and populations in South Pacific Islands, 195 poor C trachomatis diagnosis and specific treatment can result in unusually high prevalence, 194,196 probably because C trachomatis is largely asymptomatic, 4 and if untreated, shedding can persist even for years, 197 thereby increasing the potential for reinfection within couples 198 and for transmission in the population.…”
Section: Discussionmentioning
confidence: 89%
“…Previous research has shown that urine testing will miss up to 30% of endocervical C. trachomatis infections [19,29]. Interestingly, in the only published study from the PICT of non-pregnant females, urine testing showed a prevalence of 36% among women 18 to 29 years of age in Samoa [30], suggesting that genital prevalence may be even higher.…”
Section: Discussionmentioning
confidence: 98%
“…Parity, 47,48 the number of sexual partners, 49 and early sexual debut 47,49 have been previously associated with STIs/RTIs among pregnant women. No association was found between malarial and STI/RTI coinfection and factors such as parity, age, the number of sexual partners, early sexual debut, bed-net ownership, bednet use, and wealth quintile in this study.…”
Section: Discussionmentioning
confidence: 99%